2002
DOI: 10.1103/physrevb.65.233303
|View full text |Cite
|
Sign up to set email alerts
|

Crosshatching on a SiGe film grown on a Si(001) substrate studied by Raman mapping and atomic force microscopy

Abstract: The morphology, stress, and composition distributions of the crosshatch pattern on a SiGe film grown on a Si͑001͒ substrate using a low-temperature Si buffer are studied by atomic force and Raman microscopies. Crosshatching is not related to composition fluctuation regardless of the stress undulation associated with strain relaxation in the SiGe film. The crosshatch morphology arises from vertical lattice relaxation induced by piled-up misfit dislocations in the Si buffer layer and substrate. A model for cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(40 citation statements)
references
References 22 publications
4
34
1
Order By: Relevance
“…Note that the cross stripes from the Raman mapping of the Si-Si phonon of the LT-Si and Si substrate also appears. According to the previous reports [12,13], it was confirmed that this type of cross stripes corresponds to the crosshatching region due to the traveling of MDs. Moreover, the Raman images of the Si-Ge phonon of the SiGe films look very uniform despite the thickness variation.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Note that the cross stripes from the Raman mapping of the Si-Si phonon of the LT-Si and Si substrate also appears. According to the previous reports [12,13], it was confirmed that this type of cross stripes corresponds to the crosshatching region due to the traveling of MDs. Moreover, the Raman images of the Si-Ge phonon of the SiGe films look very uniform despite the thickness variation.…”
Section: Resultssupporting
confidence: 82%
“…3 (up). The bright and dark spots in the images correspond to the termination of TDs at the surface [13], which is not our interest here. At this moment, the strain relaxation of SiGe layers was speculated to be negligible, suggesting that the whole SiGe layer is pseudomorphic or coherent on LT-Si.…”
Section: Resultsmentioning
confidence: 98%
“…Raman spectroscopy is used to measure the in-plane strain (Table 2). Both un-patterned epi-growth and LAT-OVG give biaxial tensile strain [30][31][32], but when compared to the un-patterned epi-growth, strain level in LAT-OVG is smaller (Table 2) [33]. Full width half maximum (FWHM) also confirms the improvement in Ge crystal quality by employing LAT-OVG.…”
Section: Quality Of Goimentioning
confidence: 73%
“…As the thickness increases, the strain due to the lattice mismatch relaxes with the formation of misfit dislocations. The residual strain in the film is assessed by Raman spectroscopy, where the wavenumber (Raman shift) associated with the phonon peaks of Si-Si, Si-Ge, and Ge-Ge within the film are related as follows 15 : x Si-Si ¼ 520:2 À 62x À 815e cm À1 ;…”
Section: Resultsmentioning
confidence: 99%